LENDING SYSTEM WITH BRANCH PAWNING KEBAYORAN LAMA - Ikhwannurasyik Ikhwannurasyik; Susi Wagiyati P, Ir. MM (Jurnal Sistem Informasi, 1998)
Computerized systems of data processing at Pawn Service would be more efficient, effective, quick and orderly. Where the state of our current financial crisis is requiring Pawning as partners that can be used as the backbone of development. Errors that occur in data processing can be anticipated minimum. With Microsoft Access 6.0 For Windows, we can create a database application program with the view that good and interesting.